Krisis Global dan Pertumbuhan Ekonomi di Indonesia - Neli Aida; Fadeli Yusuf Afif; Tantri Siwi Peni (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2021)
This study aims to analyze the impact of the global crisis that occurred in 2008 on economic growth, the trigger for the crisis, namely an increase in credit accumulation in a large amount and in a short time in the United States (US), this increase led to an increase in bad credit so that it was quite large in the world economy. Economic growth, the global crisis, investment, exports, and labor are variables that will be obtained from the Central Statistics Agency, the Investment Coordinating Board, and others. The result of the unit root test and cointegration shows that the Error Correction Model is the chosen model. The results showed that the global crisis had a significant and negative impact on economic growth in Indonesia, while exports, labor, and investment had a significant and positive impact. Therefore, the government must maintain the balance of the economy to prevent a crisis, as well as the need to encourage investment, exports, and human resources to encourage increased economic growth.